MicroRNA deep sequencing reveals chamber-specific miR-208 family expression patterns in the human heart. (15th May 2016) - Kakimoto, Yu; Tanaka, Masayuki; Kamiguchi, Hiroshi; Hayashi, Hideki; Ochiai, Eriko; Osawa, Motoki
Abstract: Background: Heart chamber-specific mRNA expression patterns have been extensively studied, and dynamic changes have been reported in many cardiovascular diseases. MicroRNAs (miRNAs) are also important regulators of normal cardiac development and functions that generally suppress gene expression at the posttranscriptional level. Recent focus has been placed on circulating miRNAs as potential biomarkers for cardiac disorders. However, miRNA expression levels in human normal hearts have not been thoroughly studied, and chamber-specific miRNA expression signatures in particular remain unclear. Methods and results: We performed miRNA deep sequencing on human paired left atria (LA) and ventricles (LV) under normal physiologic conditions. Among 438 miRNAs, miR-1 was the most abundant in both chambers, representing 21% of the miRNAs in LA and 26% in LV. A total of 25 miRNAs were differentially expressed between LA and LV; 14 were upregulated in LA, and 11 were highly expressed in LV. Notably, the miR-208 family in particular showed prominent chamber specificity; miR-208a-3p and miR-208a-5p were abundant in LA, whereas miR-208b-3p and miR-208b-5p were preferentially expressed in LV. Subsequent real-time polymerase chain reaction analysis validated the predominant expression of miR-208a in LA and miR-208b in LV. Conclusions: Human atrial and ventricular tissues display characteristic miRNA expression signatures under physiological conditions. Notably, miR-208a and miR-208b show significant chamber-specificity as do their host genes, α-MHC and β-MHC, which are mainly expressed in the atria and ventricles, respectively. These findings might also serve to enhance our understanding of cardiac miRNAs and various heart diseases.